Multi Hazard Scenarios in the Mendoza/San Juan Provinces, Cuyo Region Argentina - Daudon, Dominique (2014)
This paper exposes major natural hazards inventory encountered in the two San Juan and Mendoza provinces, such as climatic, seismic, gravitational, and social/anthropic ones. The contrast between the high altitude of the region and low one is addressed in order to manage the inhomogeneity of prevention plans. The international road to Chile is greatly affected by gravitational hazards that proceed in out of run period and commercial traffic interruption, and large economic waste more than people vulnerability, as the urban areas are more affected by seismicity scenarios. But as gravitational hazard is affected by the seismicity it is proposed to analyze some co-hazard effect in a multi-scenarios approach from geology geography and mechanical modelling of events to explore the co-effects on the scenarios. Moreover, some similarities with the Rhone-Alpes region of France are evocated and may be of interest.